KUALITAS HIDUP PADA PASIEN DIABETES MELITUS TIPE 2 RAWAT JALAN DI RUMAH SAKIT UMUM TIDAR MAGELANG - yance anas; widi astuti r; tri murti andayani (Universitas Wahid Hasyim Semarang, 2008)
ABSTRACTDiabetes Mellitus is a chronicle disease that gives effect to patient well being. Moreover, a complication suffering gives negative effect to the patient. The aim of this research is to identify the life quality of Diabetes Mellitus (type 2) sufferer and the characteristic relating to it quality of life. This research applied descriptive design and performed on the visitors of Policlinic of the interior disease on Tidar Hospital of Magelang during Juli – August 2007. The inclusion criterion is the visitors when this research performed, entering 18 years old or more, of Diabetes Mellitus Type 2, any agreement of informed consent and filled up the questionnaire. The sample taking is done by accidental sampling. To measure the life quality is used a questionnaire of Diabetes Quality of Life (DQOL), then it continued by measure the quality of life of any patients that involved therapeutic satisfaction, the effect of therapy, the anxiety of diabetes, the anxiety of social problem and the quality of life in general. Every question is measured by the Likert Scale of 5. Of the 50 analyzed patients, 46% is female and 54% is male, with the biggest rate of age is 60-69 years old.The treatment of DM type 2 in Tidar Magelang general hospital for 50 patients who do treatment in the house have good rate life of score. It is 0,599 (it means the quality of life is higher). The lowest score of therapeutic effect is 0,588. Moreover, the highest score of anxiety to the diabetes is 0,616. The male patients and the patient with long duration show the low quality of life. Accordance with the correlation test of Spearman and Kendall is obtained that there was no significant correlation between the patient characteristic and it quality of life. Key word : the quality of life, Diabetes Mellitus Type 2, Tidar Hospital of Magelang